2020
DOI: 10.3390/ijms21155284
|View full text |Cite
|
Sign up to set email alerts
|

Shade Effects on Peanut Yield Associate with Physiological and Expressional Regulation on Photosynthesis and Sucrose Metabolism

Abstract: Intercropping improves land utilization with more crops grown together; however, shorter crops in intercropping experience stress, being shaded by the taller crops. Systematic changes in phenotype, physiology, yield, and gene regulation under shade stress in peanut are largely unknown, although shade responses have been well analyzed in model plants. We exposed peanut plants to simulated 40% and 80% shade for 15 and 30 days at the seedling stage, flowering stage, and both stages. Shade caused the increased elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
(93 reference statements)
0
19
0
Order By: Relevance
“…Based on previous studies, the genome sequences of peanut are available (Bertioli et al, 2016(Bertioli et al, , 2019Chen et al, , 2019Zhuang et al, 2019), which have facilitated the exploration of the molecular mechanisms and physiological processes in peanuts. At present, the peanut genome sequence has been used to explore the response of peanut to salt stress, the peanut shade avoidance syndrome, and peanut drought tolerance improvement (Cui et al, 2018;Chen et al, 2020;Huang et al, 2020). However, there is no report on the use of transcriptome data to explain the effect of waterlogging on peanut.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, the genome sequences of peanut are available (Bertioli et al, 2016(Bertioli et al, , 2019Chen et al, , 2019Zhuang et al, 2019), which have facilitated the exploration of the molecular mechanisms and physiological processes in peanuts. At present, the peanut genome sequence has been used to explore the response of peanut to salt stress, the peanut shade avoidance syndrome, and peanut drought tolerance improvement (Cui et al, 2018;Chen et al, 2020;Huang et al, 2020). However, there is no report on the use of transcriptome data to explain the effect of waterlogging on peanut.…”
Section: Introductionmentioning
confidence: 99%
“…When under a short period of low light stress, the size of the light harvesting antenna increased to absorb more light [32] and the expression level of LHC genes in C. sinensis and soybean were significantly induced [28,82]. Nevertheless, the enlargement of the light-harvesting antenna is limited [33] and the expression of LHC genes in Arachis hypogaea showed a downward trend under long-term light deficiency [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although M. sinostellata is a sun-loving plant, in its natural habitats, it grows under canopy shade or nearby the brook of the north slope in coniferous forest communities, and sparsely distributes in broad-leaved or mixed forest communities [7]. Canopy shade of evergreen plants in the upper layer of forest community will affect the growth of deciduous plants in the understory [9], as it alters the light intensity as well as the light quality towards a lower ratio of red/far-red light (R/FR) in the forest community [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on a large number of plant species have revealed that sucrose (Suc) is the final product of photosynthesis [5,6]. Carbohydrates originating from Suc constitute nearly 90% of the plant biomass [7].…”
Section: Introductionmentioning
confidence: 99%